A novel sex-linked microsatellite marker for molecular sexing in rock bream fish Oplegnathus fasciatus. (October 2015) - Xu, Dongdong; Lou, Bao; Li, Sanli; Sun, Xinxu; Zhan, Wei; Chen, Ruiyi; Mao, Guomin
Abstract: Sex-specific DNA markers can serve as efficient tools for molecular sex identification and thus provide important information for ecological and evolutionary studies, as well as for fishery management. In the present study, microsatellite markers were employed to identify sex-linked markers in the rock bream ( Oplegnathus fasciatus ). A microsatellite marker, designated as Oplfa16, displayed a male-specific genotype in rock bream. The male-specific microsatellite marker was further tested in 82 individuals, ensuring reproducible sex identification. Therefore, we developed a rapid and reliable method for sex identification in rock bream by using a novel sex-linked microsatellite marker. Highlights: Rock bream have differentiated sex chromosome. A novel sex-specific microsatellite marker was identified in rock bream. The sex-specific marker will a useful tool for sex identification.